Voter Registration, Turnout, and Habitual Voting Theory: The Case for Schools as Mandatory Registration Locations - Daniel Sparacino (Washington University Journal of Law and Policy, 2022)
In recent years, the United States has had extraordinarily low voter turnout compared to other liberal democracies. However, statistics suggest that this disparity can be largely attributed to lower voter registration rates. While other liberal democracies take a more active role in initiating voter registration, the United States requires individual citizens to initiate and complete the registration process. Because of this, wealthier, older, and Caucasian Americans register and vote far more often than minorities and people of lower socioeconomic status. Consequently, these disadvantaged groups have less influence than they otherwise would have over their “representatives.” In this Note, Sparacino proposes amending the National Voter Registration Act of 1993 to change the status of public schools from a discretionary voter registration location to a mandatory voter registration location to increase turnout, particularly in marginalized communities. Sparacino supports his proposal by addressing the problematic history of voter registration in America and explaining the shortcomings of alternative turnout driving proposals. The Note concludes with the argument that the NVRA amendment proposal is the best option for the United States in a time when voter registration is essential.
Keywords: Voter Turnout; Voter Registration Rates; National Voter Registration Act of 1993; Public Schools; Mandatory Voter Registration Location; Turnout; Habitual Voting Theory